In situ delivery of nanoparticles formulated with micron-sized crystals protects from murine melanoma. Issue 9 (13th September 2022) - Mohsen, Mona O; Heath, Matthew; Kramer, Matthias F; Velazquez, Thalia Carreno; Bullimore, Alan; Skinner, Murray A; Speiser, Daniel E; Bachmann, Martin F
Abstract : Introduction: Intratumoral injections of novel therapeutics can activate tumor antigen-specific T cells for locoregional tumor control and may even induce durable systemic protection (against distant metastases) via recirculating T cells. Here we explored the possibility of a universal immunotherapy that promotes T-cell responses in situ and beyond, upon intratumoral injection of nanoparticles formulated with micron-sized crystals. Methods: Cucumber mosaic virus-like particles containing a tetanus toxin peptide (CuMVTT ) were formulated with microcrystalline tyrosine (MCT) adjuvant and injected directly in B16F10 melanoma tumors. To further enhance immunogenicity, we loaded the nanoparticles with a TLR7/8 ligand and incorporated a universal tetanus toxin T-helper cell peptide. We assessed therapeutic efficacy and induction of local and systemic immune responses, including RNA sequencing, providing broad insight into the tumor microenvironment and correlates of protection. Results: MCT crystals were successfully decorated with CuMVTT nanoparticles. This 'immune-enhancer' formed immunogenic depots in injected tumors, enhanced polyfunctional CD8 + and CD4 + T cells, and inhibited B16F10 tumor growth locally and systemically. Local inflammation and immune responses were associated with upregulation of genes involved in complement activation and collagen formation. Conclusions: Our new immune-enhancer turned immunologically cold tumors into hot ones and inhibited local and distant tumor growth. This type of immunotherapy does not require the identification of (patient–individual) relevant tumor antigens. It is well tolerated, non-infectious, and affordable, and can readily be upscaled for future clinical testing and broad application in melanoma and likely other solid tumors.